Association between gestational diabetes and biomarkers: a role in diagnosis. (19th May 2018) - Adam, Sumaiya; Pheiffer, Carmen; Dias, Stephanie; Rheeder, Paul
Abstract: Background: We investigated the association between markers of insulin resistance, chronic inflammation, and adipokines and GDM. Methods: In our case-cohort study in Johannesburg we included women with GDM and controls. We tested the ability of biomarkers to identify women at high risk of GDM. Results: Of the 262 pregnant women, 83 (31.7%) had GDM. Women with GDM were heavier ( p = 0.04) and had more clinical risk factors ( p = 0.008). We found a significant difference in fasting insulin ( p < 0.001), adiponectin ( p = 0.046), HOMA ( p < 0.001) and QUICKI ( p < 0.001). HOMA (AUROC = 0.82) or QUICKI (AUROC = 0.82) improved the ability of risk factors to identify women at high risk of GDM. Conclusions : Insulin sensitivity markers are promising tools to identify women at high risk of GDM.